(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Electric vehicles are becoming popular due to their environmental benefits, but efficient charging remains a major challenge. Traditional wired charging systems require physical connections, which can lead to safety issues, maintenance problems, and inconvenience for users. To solve these issues, wireless charging technology is introduced as a modern and efficient solution.This paper presents the design and implementation of a wireless charging system for electric vehicles using magnetic resonance coupling. The system enables energy transfer without direct electrical contact. Different types of wireless charging methods such as stationary, quasi-dynamic, and dynamic charging are analyzed.The proposed system focuses on dynamic wireless charging, where vehicles can be charged while moving. Sensors and control units are used to detect vehicle presence and activate charging only when required. This improves energy efficiency and reduces power loss. The system also includes safety features like temperature monitoring and accident detection. Overall, the proposed method improves user convenience, safety, and system performance.